Effects of intrathecal injection of rapamycin on pain threshold and spinal cord glial activation in rats with neuropathic pain. (August 2015) - Lv, Jing; Li, Zhenci; She, Shouzhang; Xu, Lixin; Ying, Yanlu
<x content-type="archive" xml:space="preserve">Abstract</x> Objective: To evaluate the effects of intrathecal injection of rapamycin on pain threshold and spinal cord glial activation in rats with neuropathic pain. Methods: Healthy 30 male Sprague Dawley (SD) rats were randomly divided into six groups (n = 5 in each group): (1) control group without any treatments; (2) chronic constriction injury (CCI) group; (3) Early-rapamycin group with intrathecal injection of rapamycin 4 hours after CCI days; (4) Early-vehicle group with intrathecal injection of DMSO; (5) Late-rapamycin group with intrathecal injection of rapamycin 7 days after CCI; (6) Late-vehicle group with intrathecal injection of DMSO 7 days after CCI. Rapamycin or DMSO was injected for 3 consecutive days. Mechanical and thermal threshold were tested before and after the CCI operation. Lumbar segment of spinal cords was tested for glial fibrillary acidic protein (GFAP) by immuohistochemistry on 14th day after operation. Results: Mechanical and thermal hyperalgesia emerged on fourth day were maintained till fourteenth day after operation. After intrathecal injection of rapamycin 4 hours or 7 days after CCI, mechanical and thermal threshold significantly increased compared to injection of DMSO. The area of GFAP positive and the mean density of GFAP positive area in the dorsal horn of the ipsilateral side greatly increased in rapamycin-treated groups. Conclusions: Intrathecal injection of rapamycin may attenuate CCI-induced hyperalgesia and inhibit the activation of astrocyte.